Rain fade slope model in satellite path based on data measured in heavy rain zone - Dao, Hassan; Islam, Md Rafiqul; Al-Khateeb, Khalid A Saeed (IEEE Journal, 2013)
Rain fade slope has been measured in Kuala Lumpur,Malaysia, located in heavy rain zone. The data were collected from MEASAT3 with elevation angle of 77.4 at a frequency of 10.982 GHz with several time interval lengths. The measured fade slope was compared to the ITU-R P.1623 model. Tendency of probability distribution model and measured data is discrepant, and leading estimation of fade slope is inaccurate. Dominant parameters to the model are analyzed and proposed for the link. Modification of fade slope model has been proposed based on data with different time interval lengths’ effects.